(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and evaluate the treatment outcomes of definitive concurrent chemoradiotherapy in patients with stage II-IVA hypopharyngeal cancer. Subjects and methods: A retrospective descriptive study with longitudinal follow-up was conducted on 73 patients with stage II-IVA hypopharyngeal cancer who underwent definitive concurrent chemoradiotherapy at Nghe An Oncology Hospital from August 2020 to August 2025. Results: The mean age was 61.3 ± 6.9 years. The most common presenting symptom was dysphagia (76.7%). The primary tumor was most frequently located in the pyriform sinus (63%), and squamous cell carcinoma was the predominant histopathological type (97.3%). Stage IVA accounted for 67.1% of cases. The objective response rate was 94.5%. The mean overall survival was 35.9 ± 3.4 months, with overall survival rates of 65%, 47%, and 40% at 12, 24, and 36 months, respectively. Treatment interruption was significantly associated with poorer overall survival (p < 0.05). Conclusion: Definitive concurrent chemoradiotherapy is an effective treatment for patients with stage II-IVA hypopharyngeal cancer, achieving a high objective response rate and favorable overall survival.